Inhibition of histone methyltransferase EZH2 depletes leukemia stem cell of mixed lineage leukemia fusion leukemia through upregulation of p16. Issue 5 (30th March 2014) - Ueda, Koki; Yoshimi, Akihide; Kagoya, Yuki; Nishikawa, Satoshi; Marquez, Victor E.; Nakagawa, Masahiro; Kurokawa, Mineo
<x xml:space="preserve">Abstract</x> Leukemia stem cells (LSC) are resistant to conventional chemotherapy and persistent LSC after chemotherapy are supposed to be a major cause of relapse. However, information on genetic or epigenetic regulation of stem cell properties is still limited and LSC‐targeted drugs have scarcely been identified. Epigenetic regulators are associated with many cellular processes including maintenance of stem cells. Of note are polycomb group proteins, because they potentially control stemness, and can be pharmacologically targeted by a selective inhibitor (DZNep). Therefore, we investigated the therapeutic potential of EZH2 inhibition in mixed lineage leukemia (MLL) fusion leukemia. Intriguingly, EZH2 inhibition by DZNep or shRNA not only suppressed MLL fusion leukemia proliferation but also reduced leukemia initiating cells (LIC) frequency. Expression analysis suggested that p16 upregulation was responsible for LICs reduction. Knockdown of p16 canceled the survival advantage of mice treated with DZNep. Chromatin immunoprecipitation assays demonstrated that EZH2 was highly enriched around the transcription‐start‐site of p16, together with H3K27 methylation marks in MLL/ENL and Hoxa9/Meis1 transduced cells but not in E2A/HLF transduced cells. Although high expression of Hoxa9 in MLL fusion leukemia is supposed to be responsible for the recruitment of EZH2, our data also suggest that there may be some other mechanisms independent of Hoxa9 activation to suppress p16 expression, because expression levels of Hoxa9 and p16 were not inversely related between MLL/ENL and Hoxa9/Meis1 transduced cells. In summary, our findings show that EZH2 is a potential therapeutic target of MLL fusion leukemia stem cells.